Hyper-Aerotolerant Campylobacter coli From Swine May Pose a Potential Threat to Public Health Based on Its Quinolone Resistance, Virulence Potential, and Genetic Relatedness - Guk, Jae-Ho; Song, Hyokeun; Yi, Saehah; An, Jae-Uk; Lee, Soomin; Kim, Woo-Hyun; Cho, Seongbeom (Frontiers in Microbiology, 2021)
Campylobacter, a major foodborne pathogen, is susceptible to oxygen. Recently, aerotolerant Campylobacter with enhanced tolerance to aerobic stress has become a major concern in food safety. However, the aerotolerance of Campylobacter coli from pigs has not been studied extensively. Here, we sought to investigate the prevalence of C. coli across multiple swine groups in farms, including weaning, growing, and fattening pigs in production stages and pregnant sows. Additionally, we analyzed C. coli aerotolerance, quinolone resistance, virulence potential, and multilocus sequence typing (MLST) genotypes. Finally, we compared the characteristics of C. coli according to the aerotolerance levels. In total, we obtained 124 (66.3%) C. coli isolates from 187 swine fecal samples across six swine farms. The pathogen was prevalent in weaning (45.5%), growing (68.3%), and fattening (75.4%) pigs, and pregnant sows (66.7%). Hyper-aerotolerant (HAT C. coli (13.7% of 124 isolates) was present in all swine groups, with the highest proportion in the pregnant sows (27.3%). All HAT isolates possessed diverse virulence-related genes such as flaA, cadF, pldA, ceuE, and cdtA. All C. coli isolates were resistant to quinolones, and 12 (10%) presented high-level ciprofloxacin resistance (MIC ≥ 32 μg/mL). The proportion of C. coli isolates with a high-level ciprofloxacin resistance was the highest in HAT C. coli (18.8%). Furthermore, six MLST sequence types (STs) (ST827, ST830, ST854, ST1016, ST1068, and ST1096) of swine-derived C. coli were in common with human-derived C. coli (PubMLST). The proportion of C. coli belonging to such shared STs at each aerotolerance level was the highest in HAT C. coli (HAT vs. oxygen-sensitive; OR = 3.13). In conclusion, quinolone resistance of C. coli may be distributed throughout in all swine groups in farms. HAT C. coli is likely to remain in pig farms and re-infect other pigs in the farms. Furthermore, swine-derived HAT C. coli could be transmitted to humans easily through the food chain owing to its aerotolerance, and it could pose a threat to public health owing to its high-level ciprofloxacin resistance and virulence. This study highlights the need to develop management practices that prevent the transmission of swine-derived HAT C. coli to humans.